The Role of Higher Education in the Formation of a Healthy Lifestyle: Results of Sociological Research - A. N. Pokida; N. V. Zybunovskaya; I. A. Gazieva (Высшее образование в России)
Unfavorable demographic trends give relevance to the search of possible directions for reducing the incidence rate, strengthening the health of citizens and increasing the life expectancy of the Russian population, which is one of the priority national tasks. The COVID-19 pandemic has greatly complicated the situation by increasing population decline and causing significant damage to its health. In this regard, the activation of health care resources is of particular importance, but no less important is the attitude of people themselves to their health, manifested in the way of life, various everyday practices of behavior.The purpose of the article is to analyze, on the basis of sociological data, the dependence of the state of health of citizens, their lifestyle, various behavioral practices associated with saving and promoting health, on the presence of a high level of education. The empirical basis of the study was formed by the results of an all-Russian sociological survey conducted in 2021. The results obtained allow us to assess the potential of higher education in increasing the desire of citizens of modern Russia for self-preserving behavior and a healthy lifestyle.The results of the study show that educational groups of different status have their own characteristics of propensity to various diseases, which, quite obviously, may be associated with the lifestyle of their representatives. According to the survey, people with higher education assess their health better, care more about it, express greater awareness of the factors that determine human health, interest in a healthy lifestyle, which is manifested in more active behavioral practices aimed at maintaining and strengthening own health.